2019
DOI: 10.1021/acs.jafc.8b06465
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-Biosynthetic Study: Reactivity of Quinone Methides in the Diastereopreferential Formation of p-Hydroxyphenyl- and Guaiacyl-Type β-O-4 Structures

Abstract: p-Quinone methides are involved in lignin biosynthesis as transient intermediates, and the aromatization step has a great impact on the chemical structure of the resulting lignin. A series of quinone methides (QMs) were synthesized and allowed to react with water in pH 3–7 buffers at 25 °C to mimic the formation of p-hydroxyphenyl- and guaiacyl-type (H- and G-type, respectively) β-O-4 structures in gymnosperm-plant cell walls. Water addition occurred in 3-methoxy-substituted QMs (G-type QMs) with half-lives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 60 publications
2
29
2
Order By: Relevance
“…However, this study suggested that the reactivity of erythro form was slightly higher than that of threo form. On the other hand, in the water-addition reaction to quinone methide of I, completely opposite result was shown recently, where threo was preferentially formed more than erythro [17]. The recent study and our experiment were conducted in vitro, and thus may not perfectly be a mimic of lignin biosynthesis.…”
Section: Difference In Consumption Rates Between Erythro and Threo Iscontrasting
confidence: 84%
“…However, this study suggested that the reactivity of erythro form was slightly higher than that of threo form. On the other hand, in the water-addition reaction to quinone methide of I, completely opposite result was shown recently, where threo was preferentially formed more than erythro [17]. The recent study and our experiment were conducted in vitro, and thus may not perfectly be a mimic of lignin biosynthesis.…”
Section: Difference In Consumption Rates Between Erythro and Threo Iscontrasting
confidence: 84%
“…The α-bromo-substituting derivative of compound I, 1-bromo-2-(2-methoxyphenoxy)-1-(3,4-dimethoxyphenyl)ethane (VII, Fig. 2), was synthesized from compound I in chloroform-d by adding bromotrimethylsilane, following the method described in our previous report [25], for use as a starting compound in an acidolysis. The obtained chloroform-d solution was analyzed by 1 H-NMR to confirm its formation, disappearance of compound I, and absence of compound II.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, as described above, we conducted water addition experiments similar to those by Brunow’s group, for mimicking the formation of H-type β-O-4 structures in compression wood lignin biosynthesis . The threo -preferential water addition was observed both for H- and G-type QMs examined at pH 3.5–7.…”
Section: Introductionmentioning
confidence: 93%
“…The structural variation of QMs and their chemical properties are thought to influence the polymerization efficiency and the structure of the resulting lignins. Kobayashi et al reported in their study of monolignol oxidizability, that coniferyl alcohol (G-type) was consumed faster than p -coumaryl alcohol (H-type) in a peroxidase–H 2 O 2 system. The oxidation potentials determined by cyclic voltammetry indicated that p -coumaryl alcohol can be less oxidized than coniferyl alcohol .…”
Section: Introductionmentioning
confidence: 99%